On wh-elements in central Kurdish : a Minimalist approach - Ahmad, Salih Ibrahim (ZANCO Journal of Human Sciences., 2020)
The paper sheds light on the status of wh-elements in Central Kurdish (CK) with respect to the framework of the Minimalist Program (MP). From across the globe, there exist various types of languages whose wh-elements behave according to wh-parameter. There are languages whose wh-elements move, some others have in-situ wh-elements, and there are others in which the movement is optional. This paper aims to observe CK wh-elements in an empirical way to indicate their parametric features and their conformance to the universal principles. The notion of movement in MP is included within merge, which falls into two types: Internal merge (I-merge) and External merge (E-merge). Another important term in connection with overt movement is the Extended Projection Principle (EPP) according to which the subject position should be occupied by a phonologically expressed constituent. A fact to be known is that not all languages, among them CK, conform to this principle. The violation of certain CK wh-elements to this principle varies because they do not function in the same way. The paper presents several results revealed in the conclusion section which can be regarded as the contribution of the paper to the field of the generative syntax. One of the conclusions arrived at in the paper is that CK wh-elements are not considered as one inseparable set since they behave differently.